Development of Quibot Technology-Based Learning Media to Improve Student Motivation and Learning Outcomes - Palma Juanta; Indah Permata Sari Br Sembirinng; Liza Aulia (Journal of Technology and Informatics (JoTI), 2026)
This study examines the effect of Quibot, a chatbot-based learning medium, on students’ learning outcomes and learning motivation in mathematics learning at the junior high school level. The study was motivated by the limited integration of interactive digital media and its impact on students’ academic performance. A quantitative quasi-experimental design was employed involving 60 eighth-grade students of Yayasan Perguruan Sultan Iskandar Muda, divided into an experimental group using Quibot and a control group using conventional learning methods. Learning outcomes were measured using a validated multiple-choice mathematics achievement test, while learning motivation was assessed through a Likert-scale questionnaire. Data were analyzed using normality and homogeneity tests, followed by one-way ANOVA for learning outcomes and Welch’s t-test for learning motivation. The results showed a significant difference in learning outcomes between the two groups, F(1,58) = 4.65, p = 0.035, with a moderate effect size (η² = 0.074). However, no significant difference was found in learning motivation (p = 0.871). These findings indicate that Quibot effectively improves students’ academic achievement but does not significantly influence learning motivation within a short intervention period. This study highlights the role of chatbot-based learning media as an instrumental tool in supporting cognitive learning outcomes.